Pengaruh Beban Kerja Dan Motivasi Kerja Terhadap Turnover Intention Pegawai Di PT. Pos Indonesia Jakarta Barat (Persero) (Pada Bagian Pengantaran) - Agustian Budiarto; Muhammad Gandung (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Intention of employees at PT Pos Indonesia Jakarta Barat (Persero), specifically in the delivery division. This research employed a quantitative associative approach using a survey method. Data were collected through questionnaires distributed to 50 delivery employees and analyzed using multiple linear regression with SPSS version 31. The results indicate that Workload has a positive and significant effect on Turnover Intention, with a regression coefficient of 0.402 and a significance value of < 0.001. Meanwhile, Work Motivation does not have a significant partial effect on Turnover Intention, with a significance value of 0.196 (> 0.05). Simultaneously, Workload and Work Motivation significantly influence Turnover Intention, with a coefficient of determination (R²) of 0.526, indicating that 52.6% of the variation in Turnover Intention is explained by the model, while the remaining percentage is influenced by other factors outside this study. Therefore, proper workload management plays a crucial role in reducing employee turnover intention.